Endoplasmic Reticulum Stress-Mediated Apoptotic Pathway Is Involved in Corpus Luteum Regression in Rats. (May 2015) - Yang, Yanzhou; Sun, Miao; Shan, Yuanyuan; Zheng, Xiaomin; Ma, Huiming; Ma, Wenzhi; Wang, Zhisheng; Pei, Xiuying; Wang, Yanrong
Endoplasmic reticulum stress (ERS), which is a novel pathway of regulating cellular apoptosis and the function of ERS during corpus luteum (CL) regression, is explored. Early-luteal stage (day 2), mid-luteal stage (day 7), and late-luteal stage (day 14 and 20) were induced, and the apoptosis of luteal cells was detected by a terminal 2′-deoxyuridine 5′-triphosphate nick-end labeling (TUNEL) assay. The apoptotic cells were increased with the regression of CL, especially during the late-luteal stage. The ERS markers glucose-regulated protein 78 (Grp78), CCAAT/enhancer-binding protein homologous protein (CHOP), X-box binding protein 1 (XBP1), activating transcription factor 6α (ATF6α), eukaryotic initiation factor 2α (eIF2α), inositol-requiring protein 1α (IRE1α), caspase 12, and apoptosis marker caspase 3 were analyzed by real-time polymerase chain reaction (PCR) and immunohistochemistry, in agreement with the results of the TUNEL assay; the expression levels of CHOP, caspase 12, and caspase 3 were increased during the process of CL regression. Luteal cells were isolated and cultured in vitro, and the apoptosis of luteal cells was induced by prostaglandin F2α. The ERS was attenuated by the ERS inhibitor tauroursodeoxycholic acid, and the apoptotic rate was analyzed by flow cytometry. The ERS markers Grp78, CHOP, XBP1s, ATF6α, eIF2α, IRE1α, caspase 12, and apoptotic execute marker caspase 3 were analyzed by real-time PCR and immunofluorescence, and the results suggested that the expression of CHOP, caspase 12, and caspase 3 were increased, and there was increased apoptosis of luteal cells. But the expression of IRE1α/XBP1s and eIF2α was not detected. Taken together, the ERS is involved in the CL regression of rats through the CHOP and caspase 12 pathway.